Optimization and design of pre-reinforcement for a subsea tunnel crossing a fault fracture zone. Issue 1 (2nd January 2023) - Zheng, Yang; Wu, Ke; Jiang, Yujing; Chen, Rong; Duan, Jingchuan
Abstract: Fault fracture zones are characterized by low strength, loose rock, and poor self-stability. The lining at the contact position is prone to shear and torsion damage. During tunnel operation, shear failure of the lining under earthquake action has attracted widespread attention from researchers. However, there is a lack of clear understanding of the deformation model when a subsea tunnel crosses a fault zone under the condition of high water pressure. In this study, a 3 D-FEM model and theoretical solutions are employed to analyze the characteristics of the lining deformation and evaluate the effectiveness of different pre-reinforcement measures. The models can effectively simulate the construction process of the earth pressure balance shield (EPBS), such as the face pressure, jack force, EPBS gravity, grouting and hardening of the tail void, and they can also accurately simulate different pre-reinforcement measures, such as the umbrella arch method. The results show that the position of damage to the lining is related to the inclination angle of the fault, and the slippage of the fault causes local shear and torsion deformation of the lining. Different pre-reinforcement methods (UAM; Radial grouting; Vertical grouting) have different effects on the slippage of the fault fracture zone.